Barrelhouse Words : A Blues Dialect Dictionary - Calt, Stephen (Book collections on Project MUSE., 2009)
This fascinating compendium explains the most unusual, obscure, and curious words and expressions from vintage blues music. Utilizing both documentary evidence and invaluable interviews with a number of now-deceased musicians from the 1920s and '30s, blues scholar Stephen Calt unravels the nuances of more than twelve hundred idioms and proper or place names found on oft-overlooked "race records" recorded between 1923 and 1949. From "aggravatin' papa" to "yas-yas-yas" and everything in between, this truly unique, racy, and compelling resource decodes a neglected speech for general readers and researchers alike, offering invaluable information about black language and American slang.